An Integrative Study of Reproduction, Feeding and Behavioural Activity in Giant Transgenic Growth Hormone Mice - Perreault, Melissa (My University, 1998)
"Supermice" (TRrGH mice) contain multiple copies of rat growth hormone genes incorporated into a single chromosome. This results in double normal growth rates reaching adult body sizes twice that of normal mice. To determine how exposure to constant light (LL) affects various physiological processes, reproduction, feeding, and behaviour were examined in LL-reared TRrGH mice. Fertility, organ allometries, feeding rates, behavioural time budgets, and circadian feeding and sleep rhythms were compared for both LL and standard 12h dark: 12h light (LD). Both TRrGH and normal females exhibited a significant decrease in fertility in LL. On a mass-specific basis, TRrGH females showed increased combined ovary mass and a reduction in thymus and heart size in LL. TRrGH males demonstrated increased testes mass in LL. When adrenal size was compared between males and females, both TRrGH and normal females exhibited larger adrenals than their male counterparts in both light treatments. The fertility decrease observed in LL may have been associated with reduced food intake. LL-reared TRrGH females ate less than those in LD, although significantly more than TRrGH males in both LL and LD. When compared to normal mice, both sexes of TRrGH mice ate less in both photoperiods. The feeding rates of transgenic GLUT -4 mice were also examined. GLUT -4 mice contain double the amount of insulin responsive GLUT -4 glucose transporters which results in an increased blood glucose clearance rate. These mice, like TRrGH mice, ate less than normals, although a different age-related feeding pattern was observed. TRrGH mice in LL are behaviourally more lethargic than those reared in LD, and spend less time feeding and drinking. Circadian feeding and sleep patterns were shifted in LL by approximately 12 hours, and exhibited reduced peak amplitudes. Ultradian patterns appeared to survive the breakdown of circadian organization. TRrGH mice demonstrate a hormonal imbalance due to the excess allocation of energy into growth. It appears that, in LL, hormonal systems are further altered resulting in an increase in reproductive impairment associated with reduced feeding. One of these altered hormones may be estrogen. Hormones involved in hypothalamic-pituitary-adrenal axis (stress axis) are also implicated. It is concluded that photoperiod is important in regulating physiological processes, and TRrGH mice are more susceptible to environmental alterations due to their altered endocrinological state.
Impact of 24H Light on Physiology of Transgenic GH Mice
Keywords: integrative study; reproduction; feed; behaviour; transgenic growth hormone; mice